Um homomorfismo índice associado à ações livres de Zp - Santos Filho, João da Mata (Universidade Federal de São Carlos, 2003)
The objective of this work is to detail and to analyze consequences of a recent paper of P. Pergher, which deals with the construction of an indexhomomorphism associated to spaces equipped with free actions of the cyclic group Zp. This index-homomorphism maps the equivariant homology Zp-module of a Zp-space into Zp, and it makes possible the obtention of some results of Borsuk-Ulam type, concerning the existence of equivariant maps connecting two given Zp-spaces.
Keywords: Topologia algébrica; Teorema de Borsuk - Ulam; Homomorfismo índice; Ações livres; CIENCIAS EXATAS E DA TERRA::MATEMATICA